Cardiometabolic Risk Factors Related to Vitamin D and Adiponectin in Obese Children and Adolescents. (22nd July 2013) - Kardas, Fatih; Kendirci, Mustafa; Kurtoglu, Selim
Abstract : Obesity-related diseases are becoming the most important causes of mortality worldwide. Several studies have suggested an association between low levels of vitamin D and obesity. In addition, plasma adiponectin levels have been found to be lower in obese subjects. We evaluated the association of metabolic risk factors with both adiponectin and vitamin D levels and that between adiponectin and vitamin D levels. The study consisted of 114 obese and healthy subjects. 25-Hydroxy vitamin D [25(OH)D] levels were positively correlated with adiponectin and HDL-cholesterol (HDL-C) and inversely correlated with body mass index (BMI), LDL-cholesterol (LDL-C), total cholesterol (T-C), triglyceride (TG), fasting glucose, homeostasis model assessment of insulin resistance (HOMA index), systolic blood pressure (SBP), and diastolic blood pressure (DBP). The mean 25(OH)D levels in the obese and nonobese groups were 22.5 ± 5.7 and 32.3 ± 5.8  ng/mL, respectively (P < 0.0001 ). The mean adiponectin level in the obese group was lower than that in the nonobese group (P < 0.0001 ). Lower vitamin D and adiponectin levels were strongly associated with metabolic risk factors and obesity in Turkish children and adolescents.